Unskilled and unaware: second-order judgments increase with miscalibration for low performers - Coutinho, Mariana Veiga Chetto; Thomas, Justin; Fredricks-Lowman, Imani; Alkaabi, Shama; Couchman, Justin J. (Frontiers in Psychology, 2024)
Overestimation and miscalibration increase with a decrease in performance. This finding has been attributed to a common factor: participants’ knowledge and skills about the task performed. Researchers proposed that the same knowledge and skills needed for performing well in a test are also required for accurately evaluating one’s performance. Thus, when people lack knowledge about a topic they are tested on, they perform poorly and do not know they did so. This is a compelling explanation for why low performers overestimate themselves, but such increases in overconfidence can also be due to statistical artifacts. Therefore, whether overestimation indicates lack of awareness is debatable, and additional studies are needed to clarify this issue. The present study addressed this problem by investigating the extent to which students at different levels of performance know that their self-estimates are biased. We asked 653 college students to estimate their performance in an exam and subsequently rate how confident they were that their self-estimates were accurate. The latter judgment is known as second-order judgments (SOJs) because it is a judgment of a metacognitive judgment. We then looked at whether miscalibration predicts SOJs per quartile. The findings showed that the relationship between miscalibration and SOJs was negative for high performers and positive for low performers. Specifically, for low performers, the less calibrated their self-estimates were the more confident they were in their accuracy. This finding supports the claim that awareness of what one knows and does not know depends in part on how much one knows.